MRI Tracking of Iron Oxide Labelled Canine Mesenchymal Stem Cells in Artificial Stifle Defects - von Pueckler, Kerstin; John, Karen; Kramer, Martin; Bokemeyer, Jan; Arnhold, Stefan (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objectives The aim of this study was to describe ultrasmall superparamagnetic iron oxides labelling of canine adipose-derived mesenchymal stem cells (AdMSCs) and the detection and semiquantitative evaluation of the labelled cells after implantation in artificial canine stifle defects using magnetic resonance imaging.Methods Magnetic resonance imaging examinations of 10 paired (n = 20) cadaveric stifle joints were evaluated after creation of chondral defects and embedding of ultrasmall superparamagnetic iron oxides labelled canine mesenchymal stem cells. To prove the feasibility of the labelling for in vivo usage, Prussian blue staining, cell vitality tests and intralesional administration of labelled cells were conducted. Magnetic resonance imaging of ex vivo defects filled with different cell concentrations was obtained to depict the cell content semiquantitatively via signal intensity measurements (region of interest).Results Prussian blue staining showed that the labelling was effective. According to the vitality tests, it had no significant short-term influence on cell viability and proliferation rate. For the evaluation of the defect T2* sequences were feasible and stifle defects were visible allowing measurements of the signal intensity in all cases. Increasing the cell concentration within the chondral defects resulted in an inversely proportional, significant reduction of signal intensity according to the region of interest.Clinical Significance Ultrasmall superparamagnetic iron oxides labelling was effective. The detection of the AdMSCs in a complex anatomical structure like the surface of the femoral condyle was possible and the T2* signal intensity of the implant region was significantly correlated with the concentration of the AdMSCs.
Keywords: stem cell; MRI; tracking; dog; iron oxide